1993
DOI: 10.1128/mcb.13.1.690
|View full text |Cite
|
Sign up to set email alerts
|

A novel interferon-inducible domain: structural and functional analysis of the human interferon regulatory factor 1 gene promoter.

Abstract: We have cloned and functionally characterized the human interferon regulatory factor 1 (IRF-1) gene promoter. The promoter contains a CpG island, with several GC boxes, a CAAT box, but no TATA box. IRF-1 mRNA is strongly induced by gamma interferon (IFN-y) but more weakly and transiently by IFN-a. There are several putative KB motifs and numerous AA(G/A)G(G/T)A and GAAANN motifs throughout the promoter.The IRF-1 promoter is not autoregulated by the IRF-1 gene product. IFN inducibility of the promoter was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
194
3
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(209 citation statements)
references
References 58 publications
11
194
3
1
Order By: Relevance
“…Previous studies have demonstrated that induction of the IRF-1 gene in response to interferons and IL-6 is mediated by the binding of activated STAT-1 and STAT-3 to the palindromic GAS element present in the promoter of the IRF-1 gene (49,52,(57)(58)(59). In this report, we demonstrate that IL-12 induces IRF-1 gene transcription via activated STAT-4.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have demonstrated that induction of the IRF-1 gene in response to interferons and IL-6 is mediated by the binding of activated STAT-1 and STAT-3 to the palindromic GAS element present in the promoter of the IRF-1 gene (49,52,(57)(58)(59). In this report, we demonstrate that IL-12 induces IRF-1 gene transcription via activated STAT-4.…”
Section: Discussionsupporting
confidence: 58%
“…To analyze whether the IL-12-induced expression of IRF-1 is mediated by a specific STAT protein, we performed gel-shift experiments using a specific oligonucleotide corresponding to the GAS within the IRF-1 promoter (49,52). Total cell extracts were prepared from untreated Th1 and Th2 cells or from cells incubated with IL-12, IFN-␣, IFN-␥, and IL-4 and were used in gel-shift experiments shown in Fig.…”
Section: Stat-4 Binds To a Gas Element Within The Irf-1 Promoter-mentioning
confidence: 99%
“…It is unlikely that ISGF3 is formed after RA treatment and responsible for IFN induction, because RA is not able to stimulate the tyrosine phosphorylation of Stat1 (this paper and Matikainen et al, 1996). In addition to the GAS site (Pine et al, 1994), a putative NF-kB site has been found in the IRF-1 gene promoter (Sims et al, 1993). IFNg and TNF synergistically increase IRF-1 gene expression through the activation of Stat1 and NF-kB transcription factors respectively (Ohmori et al, 1997;Pine, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the precise mechanism of binding between the interferon regulatory factor (IRF)-1 and IFN-stimulated response element (ISRE) has been clarified (Escalante et al, 1998). In addition, the promoter of the human IRF-1 gene has been isolated and characterized (Sims et al, 1993). The IRF-1 promoter is very rich in GC and contains various nuclear factor binding domains such as CpG islands, GC boxes, putative NF-jB binding sites, and many positive regulatory domains for IFNs.…”
Section: Introductionmentioning
confidence: 99%